2005
DOI: 10.1111/j.1365-3148.2005.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions of CPDA‐1 red blood cells stored for up to 28 days decrease donor exposures in very low‐birth‐weight premature infants

Abstract: The goal of this research was to study the safety and the efficacy of transfusing citrate-phosphate-adenine anticoagulant-preservative (CPDA-1) RBC stored for up to 28 days to reduce donor exposures in premature infants. A prospective randomized two-group study was conducted with very low-birth-weight premature infants that received at least one RBC transfusion during hospital stay. Neonates randomly assigned to Group 1 (26 infants) were transfused with CPDA-1 RBC stored for up to 28 days; those assigned to Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 21 publications
4
69
0
4
Order By: Relevance
“…Second, the standard-of-care arm still received relatively fresh blood -only 12 infants received red cells that were exclusively more than 14 days old. Given that the average blood storage in the US is 18 days [1], and certain centres routinely store red cells for longer than 21 days [117], these results may not be applicable to the broader population.…”
Section: Randomised Controlled Trials (Rct)mentioning
confidence: 96%
See 2 more Smart Citations
“…Second, the standard-of-care arm still received relatively fresh blood -only 12 infants received red cells that were exclusively more than 14 days old. Given that the average blood storage in the US is 18 days [1], and certain centres routinely store red cells for longer than 21 days [117], these results may not be applicable to the broader population.…”
Section: Randomised Controlled Trials (Rct)mentioning
confidence: 96%
“…These have included healthy volunteers [67,[80][81][82], numerous retrospective and prospective observational studies [77,, and a handful of older [115][116][117][118][119][120][121][122][123], more recent [124], and ongoing randomised controlled trials. Overall, study results have been conflicting and affected by multiple methodological issues including confounding, systematic bias, limited external validity and multiple statistical shortcomings.…”
Section: Current State Of Clinical Evidence On the Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…These results should provide adequate reassurance that storage duration has no clinical impact. Several older and smaller trials,789101112131415161718192021 as well as recent meta-analyses,222324 have reported similar conclusions. However, clinical, methodological, and statistical problems may have affected the analysis and interpretation of trial results.…”
mentioning
confidence: 70%
“…Most trials have imposed thresholds for one or both groups 34. Some trials compared transfusion of cells stored for shorter and longer durations7891011121314 while others compared shorter duration with standard (blood banking) practice 1015161718192021. Half the trials included cells stored for less than seven days,89121314151617192126 even though in practice the average storage age for transfusion is 15 days .…”
Section: Definition Of the Interventionmentioning
confidence: 99%